Myxosporean phylogeny and evolution of myxospore morphotypes - Kodádková, Alena (Jihočeská univerzita, 2014)
Evolution of the Myxozoa, the group of extremely reduced metazoan parasites, has been studied on the molecular phylogenetic level for more than a decade. This thesis is focused on morphological and molecular characterization of myxozoan species with emphasis on genera with missing molecular data in GenBank as well as on revealing the hidden and cryptic species myxozoan diversity. Evolution of specific traits in myxospore morphotypes and estimation of the time of the myxozoan divergence is also investigated and further discussed.
Myxosporean phylogeny and evolution of myxospore morphotypes